When the disposition effect proves to be rational: Experimental evidence from professional traders - Guenther, Benno; Lordan, Grace (Frontiers in Psychology, 2023)
We conducted a within-subject experiment with 193 professional traders (151 professional commodities traders), to examine how the tendency towards the disposition effect varies across decision-making in mean reverting commodities and non-mean reverting equities contexts. In addition, we consider whether a simple informational intervention that makes the disposition effect salient can alter decision-making. Overall, we find that prior to the intervention the traders exhibit the disposition effect in the direction that aligns with profit maximisation goals suggesting that they are acting rational. For example, when being asked to make decisions on commodities the traders make choices in the direction of the disposition effect, which is rational given that these picks are mean reverting. We also find that the informational intervention is effective in changing the level of the disposition effect observed and also decision-making, regardless of whether traders are considering decisions over mean reverting or non-mean reverting securities. Further, we provide evidence that our simple informational intervention improves trader returns when making decisions on non-mean reverting securities only. In contrast, it has negative impacts when utilised for commodities. Our study highlights the power of simple interventions to make disproportionately large changes to decision-making regardless of whether they are in our best interests, and their beneficial role only when the context is right.